Data from: Is the continental life of the European eel Anguilla anguilla affected by the parasitic invader Anguillicoloides crassus? - Lefebvre, François (Zenodo, 2013)
Quantifying the fitness cost that parasites impose on wild hosts is a challenging task because the epidemiological history of field-sampled hosts is often unknown. In this study we used an internal marker of the parasite pressure on individual hosts to evaluate the costs of parasitism with respect to host body condition, size increase and reproductive potential of field-collected animals for which we also determined individual age. In our investigated system, the European eel Anguilla anguilla and the parasitic invader Anguillicoloides crassus, high virulence and severe impacts are expected because the host lacks an adaptive immune response. We demonstrated a nonlinear relationship between the severity of damage to the affected organ (i.e. the swimbladder, our internal marker) and parasite abundance and biomass, thus showing that the use of classical epidemiological parameters was not relevant here. Surprisingly, we found that the most severely affected eels (with damaged swimbladder) had greater body length and mass (+11% and +41%, respectively) than unaffected eels of same age. We discuss mechanisms that could explain this finding and other counter-intuitive results in this host–parasite system, and highlight the likely importance of host panmixia in generating great inter-individual variability in growth potential and infection risk. Under that scenario, the most active foragers would not only have the greatest size increase, but also the highest probability of becoming repeatedly infected –via trophic parasite transmission– during their continental life. Dataset - Lefebvre et al Raw data